Genotyping - Abdurakhmonov, Ibrokhim (IntechOpen, 2018)
Genotyping, a methodological process of detecting the allelic content of loci in a given genome, helps to reveal differences between and among individuals of comparisons. It helps in diagnostics and treatment of diseases, molecular breeding of agricultural crops, barcoding of unique biological materials, solving forensics issues, and/or controlling the spread of pathogens by tracing the origin of outbreaks. This Genotyping book aims to provide readers with an overview of the basics of genotyping process, available approaches and protocols, as well as novel, low-cost, high-throughput whole-genome genotyping tools and genotype data handling with the examples of genotyping applications in some organisms.